Adolescents with Cancer and Occupational Deprivation in Hospital Settings: A Qualitative Study - Pedro Moruno Miralles; Nieves Cedenilla Ramón; Sandra Aranda Valero (SAGE Publishing, 2016)
Objective/Background: The aim of this article was to analyze the needs of hospitalized adolescents with cancer in relation to the performance of meaningful activities as well as to explore the possible scenarios of occupational deprivation in hospital paediatric wards. Methods: The study follows an ethnographical research approach using two techniques: participant observation and in-depth interviews, with constant comparison by data triangulation. Eight adolescents diagnosed with cancer aged between 15 years and 19 years (5 males and 3 females) were recruited from Toledo and Madrid in Spain. Results: Five themes revealing the needs of adolescents with cancer in hospital environments were identified: (a) educational needs, (b) leisure needs, (c) physical space of the rooms, (d) interaction with medical personnel, and (e) lack of specific wards for adolescents. Conclusion: The lack of variety and availability of educational activities and leisure, and the subsequent changes of the individual physical, social, and cultural environments could cause situations of occupational deprivation, and also affect the health and quality of life of the individuals.